A cloned human CCAAT-box-binding factor stimulates transcription from the human hsp70 promoter. - Lum, L S (1990)
The basal promoter of the human hsp70 gene is predominantly controlled by a CCAAT element at position -70 relative to the transcriptional initiation site. We report the isolation of a novel cDNA clone encoding a 114-kDa polypeptide that binds to the CCAAT element of the hsp70 promoter. Expression of this CCAAT-binding factor (CBF) cDNA activated transcription from cotransfected hsp70 promoter-reporter gene constructs in a CCAAT-dependent manner. CCAAT-binding factor shows no homology to the previously identified human CCAAT transcription factor or rat CCAAT/enhancer-binding protein.